A Descriptive Study On Speaking Teaching - Learning Process At The Second Year Of Smk Muhammadiyah I Sukoharjo In 2010/2011 Academic Year - Pertiwi, Christina Yuniarti; , Drs. Djoko Srijono, M.Hum; , Dra. Dwi Haryanti, M.Hum (2013)
The research paper aims at describing the teaching learning process of speaking and focused the objectives of learning, the material of speaking, the procedure and activities in teaching speaking, the problem faced by the teacher and the problem faced by the students. In this study, the writer employs a descriptive qualitative research which describes the teaching learning process. The subject of this research is the eleventh grade students of SMK Muhammadiyah 1 Sukoharjo. The writer takes TKR2 class as the subject on the study. Then, the methods of collecting data are observation, interview, and document. The results of the research show that: 1) the objectives of learning speaking is the writer finds that to enable the students in understanding English as a means of communication and to enable the students in being active in being active in prating English in oral form, 2) the material of speaking is the materials of speaking at the eleventh year of SMK Muhammadiyah 1 Sukoharjo are appropriate with the competence standard in the teacher's lesson plan, 3) the procedure and activities in teaching speaking the writer finds that the classroom procedure uses three phases namely: exploration, elaboration, and confirmation. The activities in exploration are asking question, giving explanation, and giving example of the text, in elaboration, the activities is makes a group and onfirmation activities are giving explain material clearly in every meeting and giving the task as homework, 4) problems faced by the teacher are managing the time, classroom management, and the students' capability, 5) the problems faced by the students in speaking are limited vocabulary, pronunciation, grammar, the performance, nervousness.